Synthesis of (+)-muscarine from (S)-(-)-5-hydroxymethyl-2(5H)-furanone - Kang, KH; CHA, MI YOUNG; Pae, Ae Nim; Choi, Kyung Il; Cho, Yong Seo; Koh, Hun Yeong; Chung, BY (Elsevier BV, 2000)
(+)-Muscarine has been synthesized from (S)-(-)-5-hydroxy-2(5H)-furanone via rather a long pathway to provide easy access to a wide variety of its analogues. (C) 2000 Published by Elsevier Science Ltd.